Chapter 1 From Precarious Work to Sustainable Livelihoods Introduction to the Volume - Carr, Stuart (Taylor & Francis, 2024)
This volume further anchors often abstracted, global ideas like "universal decent work" within local situations, everyday work practices, and lived experiences. Relatedly, a historical strength of I/O psychology has been its focus on the diversity of sociocultural values and norms in the workplace, including at national, organizational, and individual levels (for a review, see Carr, 2013). This chapter builds on, but also constructively away from, those foundations. Specifically, this chapter-like the contributions that follow-adds to these sociocultural considerations. We do so by including diversities associated with the various socioeconomic situations of different groups that are omnipresent at the hard edges of the wage, work security, and wellbeing spectra (Carr, 2023). Finally, this chapter and book take a deep dive into "who" has been systematically excluded from decent work in the past, and how they might be systemically included in our collective and sustainable futures.